2000
DOI: 10.1161/01.str.31.9.2257
|View full text |Cite
|
Sign up to set email alerts
|

Tirilazad Mesylate in Acute Ischemic Stroke

Abstract: Background and Purpose-Tirilazad is a nonglucocorticoid, 21-aminosteroid that inhibits lipid peroxidation. Studies in experimental models of ischemic stroke had suggested that tirilazad had neuroprotective properties. As a result, clinical studies were undertaken to assess the safety and efficacy of tirilazad in the treatment of acute ischemic stroke. We performed a systematic review of randomized, controlled trials that assessed the safety and efficacy of tirilazad in patients with acute ischemic stroke. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(8 citation statements)
references
References 49 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…A second trial, using higher doses (12-15 mg/kg/day) and given within 4 h from symptom onset [159], was stopped prematurely due to safety concerns raised by TESS II, a parallel study running in Europe. A meta-analysis of trials with tirilazad concluded that the drug actually increases death and disability after ischemic stroke [160]. 4.…”
mentioning
confidence: 99%
“…A second trial, using higher doses (12-15 mg/kg/day) and given within 4 h from symptom onset [159], was stopped prematurely due to safety concerns raised by TESS II, a parallel study running in Europe. A meta-analysis of trials with tirilazad concluded that the drug actually increases death and disability after ischemic stroke [160]. 4.…”
mentioning
confidence: 99%
“…These lessons learned were fundamental in illuminating the therapeutic potential lying within microbiome research such as the use of microbial bio-active metabolites in the treatment of neurological diseases. However, the overwhelming amount of rodent-based data could not be directly translated from bench to bedside practice (Fisher et al, 1996;Mestas and Hughes, 2004;von Herrath and Nepom, 2005;Suntharalingam et al, 2006;Payne and Crooks, 2007;Seok et al, 2013;Shay et al, 2013;Garner, 2014;Hay et al, 2014;Mak et al, 2014;Wong et al, 2019;Pound and Rebecca, 2020) as we have demonstrated for AD (Zahs and Ashe, 2010;Cummings et al, 2014) and stroke (Saxena et al, 1999;Bath et al, 2000;Davis et al, 2000;Enlimomab Acute Stroke Trial Investigators, 2001;Horn and Limburg, 2001;Gertz et al, 2006;O'Collins et al, 2006;Shuaib et al, 2007;Nave et al, 2019;Pound and Rebecca, 2020). This raises the question of how the scientific community could optimize translational research models to better reflect human physiology in health and diseases.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, stroke research is highly struggling with a poor clinical translation rate and discussed in depth elsewhere (Pound and Rebecca, 2020). The vast majority of interventions for stroke successfully tested in preclinical animal studies have turned out to either have no efficacy (Horn and Limburg, 2001;Shuaib et al, 2007) or to be harmful to humans (Saxena et al, 1999;Bath et al, 2000;Davis et al, 2000;Enlimomab Acute Stroke Trial Investigators, 2001) and increased the risk of death in clinical trials. From more than 1,000 candidate neuroprotective drugs that where tested in animals, not a single one was found to benefit humans with stroke (O' Collins et al, 2006) and animal studies were just used to establish dosing but did not play a direct role in clinical translation (Pound and Rebecca, 2020).…”
Section: Microbiota and Strokementioning
confidence: 99%
“…12,59 Tirilazad was also associated with a prolonged QTc interval (increase of 7.5 ms; 95% CI, −0.8 to 15.9) and worse outcomes in patients with acute stroke. 40…”
Section: Cardiac Effectsmentioning
confidence: 99%